Communication and peace Building: the 2015 presidential elections in Nigeria (2017)
Using the discursive analytical approach, this paper examines the role of communication in peace building, and describes the pre-election and post-election strategies and interactions that enabled a peaceful environment despite the overwhelming negative campaigns and volatility of the process involving the 2015 Nigerian Presidential election campaigns. Hence, this paper illustrates the communicative behaviour of the contenders and their public display in the media which serve as a model for political peace communication; and points to the power of strategic communication for peace building, which has implications for a violence-free environment, social order and political development in Africa.